Models of improved production systems for small ruminants - Upton, M. (International Livestock Centre for Africa, 1984)
Describes models of traditional & improved small ruminant production subsystems within humid West African traditional farming systems, analysing costs & returns and factors affecting each. Includes an appendix modelling patterns of development, over time, of the size and structure of a goat flock under traditional management.